Concentrations of Campylobacter spp., Escherichia coli, Enterococci, and Yersinia spp. in the Feces of Farmed Red Deer in New Zealand. Issue 4 (1st July 2017) - Pattis, Isabelle; Moriarty, Elaine; Billington, Craig; Gilpin, Brent; Hodson, Roger; Ward, Nick
Abstract : Intensive deer farming can cause environmental issues, mainly by its impact on soils and water quality. In particular, there is a risk to the microbial quality of water, as high quantities of suspended sediment and fecal bacteria can enter into water systems. The feces of farmed red deer ( Cervus elaphus, n = 206) from Canterbury and Southland, New Zealand, were analyzed with regard to the presence of Campylobacter spp., Escherichia coli, enterococci, and Yersinia spp.. Enterococci and E. coli were isolated from all samples, with mean concentrations of 4.5 × 10 5 (95% CI 3.5 × 10 3, 5.6 10 7 ) and 1.3 × 10 8 (95% CI 1.1 × 10 6, 1.5 × 10 10 ) per gram of dry feces, respectively. Campylobacter spp. were isolated from 27 fecal samples, giving an overall prevalence of 13.1%. Campylobacter isolation rates were variable within and between regions (Canterbury 7.95% [95% CI 2–14%], Southland 16.95% [95% CI 10–24%]). Five out of 42 composite samples were positive for Yersinia enterocolitica, and one sample for Y. pseudotuberculosis. The overall prevalence ranges on a per‐animal basis were therefore 2.43 to 11.17% and 0.49 to 2.91%, respectively. This study is the first to quantify the concentration of Campylobacter spp. present in healthy deer farmed in New Zealand. Deer feces are a potential source of human campylobacteriosis, with all genotypes isolated also previously observed among human cases. The fecal outputs from deer should be regarded as potentially pathogenic to humans and therefore be appropriately managed. Core Ideas: Deer feces are a potential source of human campylobacteriosis. All Campylobacter genotypes were found among human clinical isolates in New Zealand. Campylobacter spp. prevalence in deer feces is low compared with other livestock. The average daily excretion of Campylobacter‐positive deer and sheep is comparable. Access of deer to waterways should be restricted.